A clinical decision rule for streptococcal pharyngitis management: An update - Nasirian, Hosain; TarvijEslami, Saeedeh; Matini, Esfandiar; Bayesh, Seyedehsara; Omaraee, Yasaman (Journal of Laboratory Physicians, 2017)
PURPOSE: Group A streptococcal (GAS) pharyngitis is a common disease worldwide. We aimed to establish a pragmatic program as a clinical decision rule for GAS pharyngitis diagnosis.MATERIALS AND METHODS: This article derived from a research project on children aged 6–15 years. Five hundred and seventy-one children met the enrollment criteria on whom throat culture and validities of clinical findings were assessed in positive and negative throat culture groups.RESULTS: Positive GAS throat culture group included 99 (17.3%) patients with a positive culture. Negative GAS throat culture group included 472 (82.6%) patients. Exudate or enlarged tender nodes each one had 63% and 68% sensitivity and 31.5% and 37.5% specificity with a high percentage of negative predictive value (NPV) 80.54% and 85.09%, respectively. Sequence test revealed validities of exudate plus enlarged nodes at 43.62% sensitivity and 57.19% specificity with 83% NPV.CONCLUSIONS: High NPV of 83% indicated that similar prevalence in the absence of either exudate or enlarged tender lymph nodes. Probability of GAS negative throat cultures among children suspected of GAS pharyngitis was 83% and would correctly not receive inopportune antibiotics.
Keywords: Erythema; exudate; lymph nodes; pharyngitis; streptococcal